Studies on a Hybrid Full-Bridge/Half-Bridge Bidirectional CLTC Multi-Resonant DC-DC Converter with a Digital Synchronous Rectification Strategy - Shu-huai Zhang; Yi-feng Wang; Bo Chen; Fu-qiang Han; Qing-cui Wang (Energies, 2018)
This study presents a new bidirectional multi-resonant DC-DC converter, which is named CLTC. The converter adds an auxiliary transformer and an extra resonant capacitor based on a LLC resonant DC-DC converter, achieving zero-voltage switching (ZVS) for the input inverting switches and zero-current switching (ZCS) for the output rectifiers in all load range. The converter also has a wide gain range in two directions. When the load is light, a half-bridge configuration is adopted instead of a full-bridge configuration to solve the problem of voltage regulation. By this method, the voltage gain becomes monotonous and controllable. Besides, the digital synchronous rectification strategy is proposed in forward mode without adding any auxiliary circuit. The conduction time of synchronous rectifiers equals the estimation value of body diodes’ conduction time with the lightest load. Power loss analysis is also conducted in different situations. Finally, the theoretical analysis is validated by a 5 kW prototype.